Lacanian Psychoanalytic Analysis of Film Director’s Psychological Process and Subjectivity through Filmmaking - Suthaporn, Pattanapol; Thongpibul, Kulvadee; Sakulsriprasert, Chaiyun (Journal of Behavioral Science for Development, 2022)
The objective of this study was to study and analyze the film director’s subjectivity and the psychological process through a selective use of symbols in their film, based on the Lacanian psychoanalytic approach, especially on the concepts of the three orders (the Symbolic, the Imaginary, the Real) and the desire. This research employed a qualitative method, using a case study with purposive sampling. The key informants were five auteur film directors. The data was collected through secondary resources and in-depth, semi-structured interviews, and was analyzed using thematic analysis methods. The research findings indicated three crucial themes, which were the appearance of the director’s subjectivity in the film, the dynamic of subjectivity, and growth factor and healing property. These factors have shown the director attributes in expressing their identity through movies. Furthermore, the qualities change through time, including the property of mental growth. The research findings provided some suggestion to organizations involving in psychological counseling or institutes for education to acquire a knowledge of film as a piece of art which can be utilized in an approach of expressive arts therapy, and to support an intervention development and evaluate the effectiveness of using film as a part of counseling.